Anti-Infective Pregnane Steroid from the Octocoral Carijoa riisei Collected in South Brazil - Rojo de Almeida, Maria Tereza (2012)
SUMMARY. In the present work, fractions of the ethanolic crude extract of Carijoa riisei (Octocorallia) collected at South Brazil (Santa Catarina island) were tested against different bacterial, fungal and protozoal pathogens. The n-hexane fraction (HF) showed a moderate activity against S. aureus in the disk diffusion method, and inhibited 43.4 and 35.9 % the growing of T. cruzi epimastigotes and L. braziliensis promastigotes, respectively. The steroid pregna-1,4,20-trien-3-one was isolated from HF and presented in vitro antiprotozoal activity against the extracellular forms of the parasites at 50 μM, showing 50.4 % growth inhibition of L. braziliensis and 42.4 % growth inhibition of T. cruzi.